Nutrient composition, phytochemical content and antoxidant potential of leaf extract berchemia discolor ( Munie tree) for goats in the Limpopo Province, South Africa - Molepo, Mosima Mahlogonolo (My University, 2025)
The study aims to investigate the nutrient composition, phytochemical content and antioxidant potential of leaf extract Berchemia discolor (Munie tree) for goats. Plant leaves were harvested, dried and ground. To analyse the nutrient composition, grinded leaves were taken for proximate analysis (utilizing Association of Official Analytic Chemists (AOAC) procedures), wherein they were analysed based on dry matter basis. The results revealed that protein, moisture, fat, ash, Acid Detergent Fibre (ADF) and Neutral Detergent Fibre (NDF) found in B. discolor met the requirements of goats. Based on the minerals, calcium, sodium, potassium and iron were found to have adequate amounts for goats whereas phosphorus, copper and zinc were lower. While Berchemia discolor is a valuable forage source for goat diets, its deficiencies in some minerals and other nutrients still require supplementation strategies to ensure that goats receive overall nutritional balance, thereby promoting their health and productivity. For phytochemicals and antioxidants analysis, the powder was mixed with reagents and chemicals to attain the concentration level of phytochemicals and other bioactive compounds found in these plants’ properties. Most of the phytoconstituents were present and the phenolic content, tannins and flavonoid content of B. discolor were significantly different across the treatments (P<0.05). Acetone extractant had the highest phenolic content (1.089 ± 0.06 mg/g) while water had the lowest (0.081 ± 0.06 mg/g). From the solvents used to extract active components from B. discolor leaves, DCM had the highest mass of extractants whereas acetone had a low one. Antioxidant activity was the highest quantity in the acetone extract compared to hexane, which had the lowest quantitative activity. Under FRAP, dichloromethane extract had high quantitative antioxidant activity, with water, methanol and hexane on the same low level of quantity. The results suggested that the leaves could be utilized as a feed with stronger antioxidant properties. Similarly, it was found that these bioactive compounds have effects on the health and growth performance of goats. Therefore, these phytochemicals and antioxidants protect cells from oxidative damage and enhance immune function and longevity. In conclusion, Berchemia discolor is beneficial to goats as it enhances efficiency and potentially yields to economic gains for farmers.
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2025
Keywords: Phytonutrients; Proximate analysis; Quantitative activity; Deficiencies; Extractants; Tannins; Food -- Composition; Nutrition; Peroxiredoxins; Goats; Phytonutrients; Tannins